Health Locus of Control Beliefs in Health Care Providers in the Pacific Basin - Porter, Teresa (Hawaii J Med Public Health, 2018)
As part of the strategic plan to improve preconception care, health care providers are advised to counsel women about developing a reproductive life plan. Women are asked think about whether they want to become pregnant and have children and if so, when they would like to do so. The utility of a reproductive life plan is based on the premise that an individual has control over their own health and reproduction. Less is known regarding the beliefs of health care providers which may be important for strategizing educational and training programs. We conducted this project to examine whether health care providers in the Pacific Basin region who are providing reproductive health care, believe they have control over their own health. The Multidimensional Health Locus of Control Scale was used to survey attendees of the Annual Title X Reproductive Health Conference in Saipan, Commonwealth of the Northern Marianas. The cohort of reproductive health care providers surveyed (n=21) showed high internal control scores with a mean of 29.9 (SD = 3.5) and a range of 21 to 36 (maximum score = 36) consistent with individuals who have a strong belief that their health is most influenced by their own behavior. Chance and “powerful others” scores were consistent with means noted in other studies of healthy individuals. Understanding providers' health beliefs can aid in designing and executing more effective interventions to improve reproductive health outcomes.